The priory of the orange tree : a novel - Shannon, Samantha (Bloomsbury, 2019)
The House of Berethnet has ruled Inys for a thousand years. Still unwed, Queen Sabran the Ninth must conceive a daughter to protect her realm from destruction--but assassins are getting closer to her door. Ead Duryan is an outsider at court. Though she has risen to the position of lady-in-waiting, she is loyal to a hidden society of mages. Ead keeps a watchful eye on Sabran, secretly protecting her with forbidden magic. Across the dark sea, Tané has trained to be a dragonrider since she was a child, but is forced to make a choice that could see her life unravel. Meanwhile, the divided East and West refuse to parley, and forces of chaos are rising from their sleep.--